Crashes, Volatility, and the Equity Premium: Lessons from S&P 500 Options - Santa-Clara, Pedro; Yan, Shu (The Review of Economics and Statistics, 2010)
We use a novel pricing model to imply time series of diffusive volatility and jump intensity from S&P 500 index options. These two measures capture the ex ante risk assessed by investors. Using a simple general equilibrium model, we translate the implied measures of ex ante risk into an ex ante risk premium. The average premium that compensates the investor for the ex ante risks is 70% higher than the premium for realized volatility. The equity premium implied from option prices is shown to significantly predict subsequent stock market returns.